Large-Scale Expansion of Human Mesenchymal Stem Cells - Muhammad Najib Fathi Bin Hassan; Muhammad Dain Yazid; Mohd Heikal Mohd Yunus; Shiplu Roy Chowdhury; Yogeswaran Lokanathan; Ruszymah Bt Hj Idrus; Angela Min Hwei Ng; Jia Xian Law (Hindawi Limited, 2020)
Mesenchymal stem cells (MSCs) are multipotent stem cells with strong immunosuppressive property that renders them an attractive source of cells for cell therapy. MSCs have been studied in multiple clinical trials to treat liver diseases, peripheral nerve damage, graft-versus-host disease, autoimmune diseases, diabetes mellitus, and cardiovascular damage. Millions to hundred millions of MSCs are required per patient depending on the disease, route of administration, frequency of administration, and patient body weight. Multiple large-scale cell expansion strategies have been described in the literature to fetch the cell quantity required for the therapy. In this review, bioprocessing strategies for large-scale expansion of MSCs were systematically reviewed and discussed. The literature search in Medline and Scopus databases identified 26 articles that met the inclusion criteria and were included in this review. These articles described the large-scale expansion of 7 different sources of MSCs using 4 different bioprocessing strategies, i.e., bioreactor, spinner flask, roller bottle, and multilayered flask. The bioreactor, spinner flask, and multilayered flask were more commonly used to upscale the MSCs compared to the roller bottle. Generally, a higher expansion ratio was achieved with the bioreactor and multilayered flask. Importantly, regardless of the bioprocessing strategies, the expanded MSCs were able to maintain its phenotype and potency. In summary, the bioreactor, spinner flask, roller bottle, and multilayered flask can be used for large-scale expansion of MSCs without compromising the cell quality.